Challenges in the Electrochemical Synthesis of Si2Cl6 Starting from Tetrachlorosilane and Trichlorosilane. Issue 1 (3rd January 2022) - Beck, Alexander D.; Haufe, Stefan; Tillmann, Jan; Waldvogel, Siegfried R.
Abstract: The strongly increasing demand for nano‐ and microelectronics calls for new and environmentally benign reaction pathways for the preparation of one of the most important substrates in the production of semiconductor materials: Si2 Cl6 . We present a comprehensive study of the opportunities and challenges for the selective electrochemical formation of higher halo‐functionalized silanes to Si2 Cl6 achieved by cyclic voltammetry measurements and electrochemical synthesis. Cathodic dehalo‐dimerization reaction of SiCl4 and the approach to halogen exchange for better substrate reduction are envisioned. An anodic halide‐free dimerization pathway by dehydrogenation of HSiCl3 is investigated, including Lewis acid activation of the Si−H bond. In addition, tertiary amine‐driven, Benkeser‐like in‐situ formation of a SiCl3 − anion was tested as well. The target molecule Si2 Cl6 is strongly promoted to direct electro‐conversions making the anodic and cathodic electrosynthesis very challenging. Abstract : Opportunities and challenges : A comprehensive study on the selective electrochemical formation of Si2 Cl6 starting from higher functionalized halosilanes is reported. Reductive dehalo‐dimerization and oxidative dimerization by dehydrogenation are tested, including Lewis acid activation and tertiary amine‐driven strategies for Si−H bond activation. Both pathways promote the formation of oligomeric halosilanes.